What palliative care can do for motor neurone disease patients and their families - Oliver, D.; Aoun, Samar (Hayward Medical Communications, 2013)
Appropriate palliative care is essential for people with motor neurone disease, a progressive and irreversible neurological condition that can have distressing symptoms in its later stages. David Oliver and Samar Aoun detail how and when the specialist palliative care team should get involved.